Quantitative MR Analysis of Changes in the Radius Bone Marrow in Osteoporosis - Tamar K. De-Levie; Yael S. Schiffenbauer; Ido Druckmann; Vanessa Rouach; Naftali Stern; Itzhak Binderman; Uri Nevo (Journal of Osteoporosis)
Purpose. This pilot study aimed to explore the feasibility of scanning the human distal radius bone marrow in vivo to detect osteoporosis-related changes using magnetic resonance and evaluate whether the radius may serve as an accessible probing site for osteoporosis. This may lead in the future to the use of affordable means such as low-field MRI scanners for the monitoring of disease progression. Methods. A clinical trial was performed using a 3T MR scanner, including 26 women assigned into three study groups: healthy-premenopausal (n = 7; mean age 48.6 ± 3.5 years), healthy-postmenopausal (n = 10; mean age 54.5 ± 5.6 years), and osteoporotic-postmenopausal (n = 9; mean age 61.3 ± 5.6 years). Marrow fat composition was evaluated using T2 maps, a two-compartment model of T1, and a Dixon pulse sequence. Results. The osteoporotic group exhibited higher fat content than the other two groups and lower T2 values than the healthy-premenopausal group. Conclusions. Osteoporosis-related changes in the composition of the distal radius bone marrow may be detected in vivo using MRI protocols. The scanning protocols chosen here can later be repeated using low-field MRI scanners, thus offering the potential for early detection and treatment monitoring, using an accessible, affordable means that may be applied in small clinics. This trial is registered with MOH_2018-05-23_002247, NCT03742362.